Oral administration of Aristolochia manshuriensis Kom in rats induces tumors in multiple organs. (28th October 2018) - Wang, Lianmei; Ding, Xiaoshuang; Li, Chunying; Zhao, Yong; Yu, Changan; Yi, Yan; Zhang, Yushi; Gao, Yue; Pan, Chen; Liu, Suyan; Han, Jiayin; Tian, Jingzhuo; et al.
Abstract: Ethnopharmacological relevance: Aristolochia manshuriensis Kom (AMK), belonging to the Aristolochia family, is traditionally used in China to remove heart fire, promote dieresis, restore menstruation, and enhance milk secretion. The active constitutes of AMK are aristolochic acids (AAs, I and II) that are reported to cause serious side effects including nephrotoxicity and carcinogenicity. Aim of the study: The tumorigenic role of AMK is far to be understood. We analyzed the toxicity reactions after long-term exposure of AMK in rats. Materials and Methods: Sprague–Dawley rats underwent gavage with AMK doses of 51 mg/kg (AMK-1), 253 mg/kg (AMK-2), 508 mg/kg (AMK-3), 1029 mg/kg (AMK-4) or AAs of 15 mg/kg (AAs), and then sacrificed at the 6th, 10th, 14th, 18th, 22th, 26th and 30th weeks. Endpoint measurements included clinical observations, body weights, blood biochemistry, haematology and histomorphological observations. Results: Body weight decreased after AMK or AAs treatment in rats. AMK destroyed renal function, and induced anemia in rats. AMK caused kidney, stomach, bladder and subcutaneous tumors in rats. In addition, primary hepatic carcinoma was not observed in rats. Conclusions: AMK had significant toxic effects in rats with regard to decreased body weight, diminished renal function, increased anemia and tumor incidence. Kidney, stomach, bladder and subcutaneous tissue are carcinogenic target organs of AMK or AAs, however liver is no- carcinogenic target organ of AMK or AAs in rats. AMK is carcinogenic in rats, and not be safe for humans. Graphical abstract: